(untitled) (Research, Society and Development, 2021)
Purpose: To assess the prevalence and risk factors for self-injury and suicide attempt in prison in a sample composed of 186 female inmates. Methods: Sociodemographic data, measures of depression, self-destructive behavior, suicide attempt, and other specific questions related to the reality in the prison environment were collected. Results: Self-injury and suicide attempt before incarceration was reported by 11.3% and 35.5% of the sample, respectively. During imprisonment, a prevalence of 29% and 18.8% for self-injury and suicide attempt, respectively, was observed. Multiple binary logistic regression identified the following risk factors for self-injury: age <32 years, depressive symptoms, history of torture at the time of the arrest, aggression in prison, and sexually transmitted infection. Conversely, the risk factors for suicide attempt were depressive symptoms, self-injury history, aggression in prison, and sexually transmitted infection. Conclusion: This study confirmed the high prevalence of self-harm and suicide attempts in female prisoners. Specific screening tools and the institution of public policies to assess and provide mental health care for incarcerated people in Brazil are needed.